Pengaruh Perlakuan Panas Terhadap Sifat Fisis Dan Mekanis Pada Hasil Pengelasan Baja Tahan Karat Aisi 420 - Perpustakaan UGM, i-lib ([Yogyakarta] : Unit Informasi Inovasi Proses Pembelajaran (UI2P2) Universitas Gadjah Mada, 2003)
,The objective of this research is to investigate the effect of heat treatment on tensile stress and hardness of welded AISI 420 stainless steel. The electrode type of E 312 was used. The current and voltage were set to 100A and 29V, respectively. The welded specimen was treated at 1050"C during 25 minutes and subsequently quenched in the oil medium. The quenched specimen -was-then heated at 600Â°C during 2 hours and cooled M the air medium. . . The hardness distribution the cross surface shows that the highest one at the base metal is about 33,11% and 10,94% for, quenched and without quenched specimens, respectively. The hardness decreased- due to quenching and annealing is about 8,27% compared to that of the base material. The hardness decreased due to quenching and.annealing continued with tempering is 2,47% and 5,21% for hardening â¢ and quenching specimens, respectively. Similarly, The haidness.decreased at.the HAZ dui, to quenching and annealing is 15,48% and 5,21%, respectively. . - The -tensile test- result-shows that the welded specimen increases about 1,95%. On the other hand, the ultimate stietigth deereaSes about 80.31% and 31,92% for quenching and tempering specimens.